HOW TO IMPROVE INNOVATION CAPABILITY? : THE ROLE OF INTELLECTUAL CAPITAL AND ORGANIZATIONAL MOTIVATION OF MANUFACTURING FIRMS IN SRI LANKA - Sivalogathasan, V. (University of Jaffna, 2016)
The intellectual capital creates a crucial factor for the achievement of the innovation of firm. Numerous studies have been documented that intellectual capital positively influences innovation capability, which is conceptualized as the degree to achieve its firm performance. However, there is a lack of studies examining the specific means through which organizational motivation influences innovation capability at firm level. Therefore, the purpose of this study is to exhibit the Intellectual capital effects on firm innovation capability by influence the organizational motivation. This study investigates the multidimensional and contingent gradual effect of intellectual capitals and organizational motivation on innovation capability. Manufacturing sectors have shown commendable progress over the past few decades in Sri Lankan. The structured questionnaires were administrated as a research instrument and random sampling technique was used to collect the data from 462 senior executives and senior managers from manufacturing firms in Sri Lanka. The study revealed that the intellectual capital have significant positive relationship on innovation capability with strong influence of organizational motivation. The intellectual capital mediated by organizational motivation that lies outside and inside of the firm have an indirect effect on innovation capability. The findings of this study will be useful for manufacturing industry to apply intellectual capital management and identify organizational motivation to create innovation in their organizations.
Keywords: Intellectual capitals; Innovation capability; Organizational motivation